Estudo multitemporal da dinâmica espacial do estuário Potengi/RN, utilizando como base os dados de sensoriamento remoto. - Medeiros, Maria Lúcia de (2009)
This work was developed in the Potengi river estuary, northern coastal city of Natal, located in the State of Rio Grande do Norte. The objective was to study the dynamics of Multitemporal Space in that estuary, however, analyze how this environment has behaved during the years 1988, 1994 and 2006. The definition of that, there was the fact that during that period, which occurred in that area and more intensive space exploration to practice economic activities as well as a greater and more rapid expansion of urban area. This study was supported by the Remote Sensing, who have been shown today, as an efficient analysis of the environmental studies, through geoprocessing techniques. From the performed analysis it was found that occurred during the period of study (1988 to 2006), a huge change in the design of the estuary of Potengi river. The figures showed the area of vegetation was decreased 65.22%, the deforested area increased by 70.44% and the shrimp activity grow 452.07% and the urban area was increased in 52.65% along that period described. Considering the numbers shown there that the process of occupying space in that area requires attention, because it is an environment that represents a huge contribution to the ecological balance.